Thermodynamics - based method for estimating solar PV yield using Philippines SSE and PV performance paramaters - Buhali, Mario L. Jr. (2013)
The Department of Energy has determined the amount of solar energy in the Philippines to have an average value of 5.5 kilowatt-hours per square meter. Methods of estimating the amount of solar photovoltaic (PV) yield from this average value vary, each having distinct level of accuracy. Solar panel efficiencies rated at standard test conditions (STC) identified by the International Electrotechnical Commission (IEC) are being used widely to perform preliminary estimates of PV yield. Years of practice have proven this method as insufficient. More standards and methods have emerged since then. This study proposes using surface meteorology and solar energy (SSE) together with PV performance parameters to estimate solar PV yield in Philippine outdoor conditions in a method based on the Laws of Thermodynamics. The difference between rated performance and actual performance is conceptualized based on the Second Law. A framework for using SSE data and PV performance parameters in the first law equation for a closed, rigid system is also established. This method was validated by 10 days of continuous testing last September 2012 at a PV installation on the roof deck of the Electrical and Electronics Engineering Institute at the University of the Philippines, Diliman. An average actual efficiency and derate factor were determined using SSE and electrical parameters measured from the first day and were used to estimate the yield for the next nine days of varying weather conditions.
Thesis (M.S. Energy Engieering)--University of the Philippines, Diliman
Keywords: Solar energy